Effect of Styrofoam Waste Substitution on the Performance of Asphalt Concrete Wearing Course in Cattle Manure Immersion - Liza Afra; Nura Usrina; Khairul Amna; Zulfhazli Abdullah; Mukhlis Mukhlis (Electronic Journal of Education, Social Economics and Technology, 2025)
Cow feces on roads causes damage to asphalt on highways because cow feces contains a large amount of nutrients. The use of Styrofoam in asphalt is expected to improve the technical properties of a mixture. This study aims to determine the Marshall characteristics of asphalt concrete (AC-WC) mixtures with 5%, 7%, and 9% Styrofoam waste additions in 60/70 asphalt against asphalt weight with cow feces immersion for 30 minutes, 24 hours, and 48 hours. The best stability value was obtained with a 5% Styrofoam substitution, which was 1972.55 kg. The parameters for mixtures with and without Styrofoam, including stability, flow, MQ, density, VIM, VMA, and VFA, still meet the specifications of the 2018 Bina Marga standards. The durability value without substitution was 92.64% with ordinary water immersion and 90.80% with cow feces immersion. The durability value with varying Styrofoam percentages 5% was 95.56% and met the specifications set by Bina Marga in 2018, which is ≥ 90%.